Exclusion of RET and Pax 3 loci in Waardenburg-Hirschsprung disease. Issue 4 (April 1995) - Attié, T; Till, M; Pelet, A; Edery, P; Bonnet, J P; Munnich, A; Lyonnet, S
Abstract : The RET and the Pax 3 genes have recently been shown to account for autosomal dominant Hirschsprung's disease (HSCR) and Waardenburg syndrome type 1 (WS1) respectively, which led us to consider them as candidate genes in the WS/HSCR association. Linkage analyses performed in a consanguineous WS/HSCR family support the view that neither the RET locus nor the Pax 3 locus are involved in the disease phenotype. Hence, at least one further locus altering neural crest cell development is responsible for the pleiotropic features observed in the WS/HSCR association.